Unplanned hospital readmissions after kidney transplantation among patients in Hefei, China: Incidence, causes and risk factors - Aiqin Chu; Tian Zhang; Yueyan Fang; Li Yuan; Xiaohong Guan; Hailing Zhang (Elsevier, 2020)
Objectives: Unplanned readmissions severely affect a patient's physical and mental well-being after kidney transplantation (KT), which is also independently associated with morbidity. A retrospective study was conducted to identify the incidence, causes and risk factors for unplanned readmission after KT among Chinese patients. Methods: Patients who underwent KT were admitted to the organ transplant center of the Affiliated Hospital of University of Science and Technology of China (2017-2018). Medical records for these patients were obtained through the hospital information system (HIS). Results: In 518 patients, the incidence of unplanned readmissions within 30 days (n = 9) was 1.74%, and 90 days (n = 64) was 12.35%. The one-year unplanned readmission rate was 22.59% (n = 122). Overall, 122 patients were readmitted because of infection, renal events, metabolic disturbances, surgical complications, etc. Hemodialysis (OR = 10.462, 95% CI: 1.355-80.748), peritoneal dialysis (OR = 8.746, 95% CI: 1.074-71.238) and length of stay (OR = 1.023, 95% CI: 1.006-1.040) were independent risk factors for unplanned readmissions. Conclusion: Unplanned readmission rates increased with time after KT. Certain risk factors related to unplanned readmissions should be deeply excavated. Targeted interventions for controllable factors to alleviate the rate of unplanned readmissions should be identified.